The effect of nano-scale topography on osteogenic differentiation of mesenchymal stem cells - Faghihi, Faezeh; Baghaban Eslaminejad, Mohamadreza (Biomedical papers, 2014)
Background: Large bone defects resulting from trauma or disease pose a threat to humans. Thus far, tissue engineering as an important clinical approach uses cells, growth factors and scaffolds to regenerate large areas of damaged bone tissue. Since bone is a nanocomposite structure, it is assumed that nanomaterial scaffolds can induce or promote osteogenesis by mimicking the cell niche at nano level.Methods and Results: In this review we highlighted the effect of nano-scale topography on osteogenic differentiation of Mesenchymal Stem Cells (MSCs) as potent cell candidates in bone engineered constructs. The key point in the induction of differentiation by nanomaterials is the discontinuity in their topography. This leads to alteration in protein adsorption and restriction of extracellular matrix deposition by the cells and consequently leads to changes in cell morphology and the frequency of accessible sites for cell adhesion. Here, we have reviewed the literature on the role of different types of nanomateial scaffolds in osteogenic differentiation of these cells. Since little is known about the underlying molecular networks induced by nanomaterials, we also reviewed possible underlying mechanisms of nanotopographical effects on the osteogenic differentiation of MSCs.Conclusions: Nano-scale materials provide a niche which is very similar to native bone in geometry and stiffness. Such nano-scale topographies improve the function of MSC-based engineered constructs in regeneration of bone defects.
Keywords: mesenchymal stem cells; bone tissue engineering; nano-scale topography; osteogenic differentiation